Patterns of Juvenile Delinquency and Co-Offending in Philadelphia, Pennsylvania, 1976-1994 - McCord, Joan ([Verlag nicht ermittelbar], 2004)
In an attempt to inform and advance the literature on co-offending, this study tracked through time the patterns of criminal behavior among a sample of offenders and their accomplices. This study consists of a random sample of 400 offenders selected from all official records of arrest (N=60,821) for offenders under age 18 in Philadelphia in 1987. Half of the offenders selected committed a crime alone and half committed a crime with an accomplice. Criminal history data from January 1976 to December 1994 were gathered for all offenders in the sample and their accomplices.